2023
DOI: 10.3390/polym15153324
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Nanocellulose from Polyester–Cotton Textile Waste for Modification of Film Composites

Preeyanuch Srichola,
Kuntawit Witthayolankowit,
Prakit Sukyai
et al.

Abstract: Textile waste has emerged as a critical global challenge, with improper disposal practices leading to adverse environmental consequences. In response to this pressing issue, there is growing interest in recycling textile waste containing cellulose as an alternative approach to reducing the impact of industrial waste on the environment. The objective of this research is to investigate the extraction and characterization of nanocellulose from polyester–cotton textile waste as a potential solution to address the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
1
2
1
Order By: Relevance
“…The calculated crystallite size did not exhibit significant variations, yet the TEM images provided a more intricate measurement of the crystallite size. The dimensions of the crystalline regions were in accordance with values that have been previously published [ 16 , 50 , 52 ]. The (200) and (1–10) diffraction peaks exhibit associated d-spacings and relative intensities that are associated with the arrangement of β-1,4-linked glucan chains that form the crystalline lattice of CNCs.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The calculated crystallite size did not exhibit significant variations, yet the TEM images provided a more intricate measurement of the crystallite size. The dimensions of the crystalline regions were in accordance with values that have been previously published [ 16 , 50 , 52 ]. The (200) and (1–10) diffraction peaks exhibit associated d-spacings and relative intensities that are associated with the arrangement of β-1,4-linked glucan chains that form the crystalline lattice of CNCs.…”
Section: Resultssupporting
confidence: 88%
“…Zhong et al [ 26 ] also observed comparable patterns, where the inclusion of 5% CNC derived from indigo-dyed cotton waste resulted in a significant enhancement of the tensile characteristics of the PVA film. Our findings on tensile strength and elongation exhibited superior outcomes compared to the data presented by Srichola et al [ 52 ]. In their study, the tensile strength was recorded at 2.37 MPa with a 5% nanocellulose loading.…”
Section: Resultscontrasting
confidence: 64%
“…As well, nanocellulose fibres have shown potential applications beyond textile dyeing, including paper and textile coating, as well as the fabrication of film composites [80,81]. Nanocellulose may be derived from plant fibres or algae, and its efficacy is attributed to its little thermal expansion, as shown by previous research [82].…”
Section: B Nanocellulose-based Hydrogelsmentioning
confidence: 89%
“…Other authors analyzed the proportion of fabric quality based on recycled fibre yarns; for this, the following prototypes were created in 100% FAR, 100% VCF, 35% polyester -65% RCF, 35% polyester -65% VCF, 50% VCF -50% polyester and 50% RCF -50% polyester, the adequate proportion was 50% RCF -50% polyester, which presented 79 defects [34], the lower the defect present in the fabric, the higher it's quality according to the Graniteville 78 system, which evaluates the defects and quality of https://doi.org/10.31881/TLR.2023.184 the fabric, which rated the proportion 50% RCF -50% polyester as acceptable. Other more recent studies used hydrolysis to be able to mix other types of fibres other than 35% polyester with 65% cotton with PET to improve the properties of the fibres [35] and 60% cotton with 40% PET [36].In addition, it is essential to mix recycled fibres with virgin fibres in a particular proportion so that the properties of the yarn are better and the fabric presents fewer defects; from the sample of 54 fabrics produced, ten were evaluated, and the author suggests the mixture of 50% VCF and 50% RCF as the adequate [37], for this it is required to separate the textures and fibre type of the materials, to achieve a quality as if new raw materials were used. Moreover, the yarn behaviour in elongation and strength criteria are adequate [38].…”
Section: Specific Objectives (So)mentioning
confidence: 99%